Support network: the challenges of ensuring myocardial infarction patients comfort in the critical care unit: a qualitative study - Simin Hojjatoleslami; Seyed Reza Borzou; Reza Negarandeh; Ali Reza Soltanian; Amir Sadeghi (BMC, 2024)
Abstract Introduction Myocardial infarction (MI) is a critical emergency condition that affects all aspects of health. Patients with MI need specialized care in the Coronary care unit (CCU). The main goal of care is to ensure their comfort, which can be significantly affected by their illness and hospitalization. This study aims to explore MI patients' perceptions of support network challenges to ensure comfort in the CCU. Methods A qualitative approach was adopted, and semi-structured interviews and notes were used for collecting data between 2020 and mid-2021. The participants were 27 MI patients in our country who had been hospitalized in the CCU of the University Heart Hospital. They were selected using purposive sampling. The data were analyzed using conventional content analysis by Graneheim and Lundman. Findings The results of this research were revealed in the form of a "support network" theme comprising five categories: "Physical support", "Mental occupations", "Presence of peers", "relatives support "and "Spiritual strategies". Conclusion The study results showed that MI patients, in critical condition, receiving care, and hospitalized in the CCU require continuity in their support network to ensure comfort. The inconsistency between the components of each dimension leads to the challenge of ensuring comfort.